Depression with Comorbid Diabetes: What Evidence Exists for Treatments Using Traditional Chinese Medicine and Natural Products? - Yanting Lu; Yanting Lu; Tao An; Hu Tian; Xueqin Gao; Furong Wang; Shijun Wang; Shijun Wang; Ke Ma; Ke Ma (Frontiers Media S.A., 2021)
Comorbidity between diabetes mellitus (DM) and depression, two chronic and devastating diseases spreading worldwide, has been confirmed by a large body of epidemiological and clinical studies. Due to the bidirectional relationship between DM and depression, this comorbidity leads to poorer outcomes in both conditions. Given the adverse effects and limited effectiveness of the existing therapies for depression associated with diabetes, the development of novel therapeutic drugs with more potency and fewer side effects is still the most important goal. Hence, many researchers have made great efforts to investigate the potential usefulness of traditional Chinese medicine (TCM) and natural products, including natural extracts and purified compounds, in the treatment of comorbid depression in diabetes. Here, we reviewed the related literature on TCM and natural products that can remedy the comorbidity of diabetes and depression and presented them on the basis of their mechanism of action, focusing on shared risk factors, including insulin resistance, oxidative stress and inflammation, and nervous disturbances. In short, this review suggests that TCM and natural products could expand the therapeutic alternatives to ameliorate the association between DM and depressive disorders.